Pengaruh Ukuran Kantor Akuntan Publik, Likuiditas, dan Profitabilitas Terhadap Audit Delay - Mhd Hasan Pasaribu; Riva Ubar Harahap (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aims to analyze the factors that affect audit delay in the form of KAP size, liquidity, and profitability. The type of research itself is associative with a sample of 17 property and real estate companies listed on the Indonesia Stock Exchange (IDX). The selection of this case is based on the pandemic conditions that hit the entire world in the period 2019 to 2021 where investment focused a lot on sectors that are more crucial than investment in property and real estate, so curiosity arose about the impact of the pandemic on this sector, especially in its changes. The research was conducted on the Indonesia Stock Exchange (IDX) located in the city of Medan so that it can be understood that the data used is secondary data / not raw data. The data used in this study is a time series covering 2019 to 2021 totaling 51 data. Data analysis analysis techniques use logistic regression analysis which includes Partial Model Significant Test, Simultaneous Testing (Omnibus). The results of the research conducted showed that: 1) The size of the KAP did not have a significant effect on the audit delay; 2) Liquidity has no significant effect on audit delay; and 3) Profitability does not affect audit delay, but all three simultaneously affect audit delay in property and real estate sector companies that have been listed on the Indonesia Stock Exchange.